Question

3) If f=f(x, y), derive a forward finite difference approximation of 3rd order accuracy, O(h³), for...

3) If f=f(x, y), derive a forward finite difference approximation of 3rd order accuracy, O(h³), for ∂f/∂x.

Homework Answers

Know the answer?
Your Answer:

Post as a guest

Your Name:

What's your source?

Earn Coins

Coins can be redeemed for fabulous gifts.

Not the answer you're looking for?
Ask your own homework help question
Similar Questions
Use forward and backward difference approximations of O(h) and a centered difference approximation of O(h^2 )...
Use forward and backward difference approximations of O(h) and a centered difference approximation of O(h^2 ) to estimate the first and second derivatives of f(x)= 0.4x^5 ‐0.2x^3 +6x^2 ‐13 at x=2 using a step size h=1. Repeat the computation using h values of 0.5, 0.25, and 0.1. Compare your results with the exact derivative value at x=2.
Taylor series f(xi+1)=f(xi)+f'(xi)h+(f''(xi)/2!)h2+(f'''(xi)/3!)h3+..... given f''(xi)=(-f(xi+3)+4f(xi+2)-5f(xi+1​)+2f(xi))/h2 derive the second derivative of forward finite difference n=3 what is...
Taylor series f(xi+1)=f(xi)+f'(xi)h+(f''(xi)/2!)h2+(f'''(xi)/3!)h3+..... given f''(xi)=(-f(xi+3)+4f(xi+2)-5f(xi+1​)+2f(xi))/h2 derive the second derivative of forward finite difference n=3 what is the order of error
Taylor series f(xi+1)=f(xi)+f'(xi)h+(f''(xi)/2!)h2+(f'''(xi)/3!)h3+..... given f''(xi)=(-f(xi+3)+4f(xi+2)-5f(xi+1​)+2f(xi))/h2 derive the second derivative of forward finite difference  
Taylor series f(xi+1)=f(xi)+f'(xi)h+(f''(xi)/2!)h2+(f'''(xi)/3!)h3+..... given f''(xi)=(-f(xi+3)+4f(xi+2)-5f(xi+1​)+2f(xi))/h2 derive the second derivative of forward finite difference  
Derive or prove the three point backward difference approximation of the first derivative, aka Dh--f, of...
Derive or prove the three point backward difference approximation of the first derivative, aka Dh--f, of a function f(x), using either polynomial interpolant method (Newton's or Lagrange's) here is the first derivative approximation: f'(x) = (3* f(x) - 4*f(x-h)+ f(x-2h)) /2h , which is congruent to Dh--f
Consider the function f(x) = sin(x). Suppose we want to approximate f 0 (0) by using...
Consider the function f(x) = sin(x). Suppose we want to approximate f 0 (0) by using a forward difference approximation and a stepsize of h. How small must h be in order to guarantee that the absolute error in our approximation is less than 0.01?
Let f(x,y)=xcos(πy)−ysin(πx)f(x,y)=xcos⁡(πy)−ysin⁡(πx). Find the second-order Taylor approximation for ff at the point (1, 2).
Let f(x,y)=xcos(πy)−ysin(πx)f(x,y)=xcos⁡(πy)−ysin⁡(πx). Find the second-order Taylor approximation for ff at the point (1, 2).
-find the differential and linear approximation of f(x,y) = sqrt(x^2+y^3) at the point (1,2) -use tge...
-find the differential and linear approximation of f(x,y) = sqrt(x^2+y^3) at the point (1,2) -use tge differential to estimate f(1.04,1.98)
1) Use finite approximation to estimate the area under the graph of f(x) = x^2 and...
1) Use finite approximation to estimate the area under the graph of f(x) = x^2 and above the graph of f(x) = 0 from Xo = 0 to Xn= 2 using i) a lower sum with two rectangles of equal width ii) a lower sum with four rectangles of equal width iii) an upper sum with two rectangles of equal width iv) an upper sum with four rectangles if equal width 2) Use finite approximation to estimate the area under...
Prove the following : (∃x)(F(x)⋀(G(x)⋁(H(x)))→(∃x)(∃y)(F(x)⋀(G(y)⋁H(y)))
Prove the following : (∃x)(F(x)⋀(G(x)⋁(H(x)))→(∃x)(∃y)(F(x)⋀(G(y)⋁H(y)))
Let f(x) = 3x^2+x. Find the difference quotient. f(x+h)-f(x) / h
Let f(x) = 3x^2+x. Find the difference quotient. f(x+h)-f(x) / h